Nanophotonic biosensors harnessing van der Waals materials - Sang-Hyun Oh; Hatice Altug; Xiaojia Jin; Tony Low; Steven J. Koester; Aleksandar P. Ivanov; Joshua B. Edel; Phaedon Avouris; Michael S. Strano (Nature Communications, 2021)
This review presents an overview of scenarios where van der Waals (vdW) materials provide unique advantages for nanophotonic biosensing applications. The authors discuss basic sensing principles based on vdW materials, advantages of the reduced dimensionality as well as technological challenges.